2021
DOI: 10.1038/s41598-021-84817-2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological targeting of host chaperones protects from pertussis toxin in vitro and in vivo

Abstract: Whooping cough is caused by Bordetella pertussis that releases pertussis toxin (PT) which comprises enzyme A-subunit PTS1 and binding/transport B-subunit. After receptor-mediated endocytosis, PT reaches the endoplasmic reticulum from where unfolded PTS1 is transported to the cytosol. PTS1 ADP-ribosylates G-protein α-subunits resulting in increased cAMP signaling. Here, a role of target cell chaperones Hsp90, Hsp70, cyclophilins and FK506-binding proteins for cytosolic PTS1-uptake is demonstrated. PTS1 specific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(49 citation statements)
references
References 72 publications
0
47
0
Order By: Relevance
“…For example, it is not known how the unfolded PTS1 regains its active conformation in the cytosol. However, a crucial role of cellular protein folding helper enzymes for uptake of PTS1 into the host-cell cytosol has been demonstrated (see Section 3.1 ) [ 41 , 42 , 43 ].…”
Section: Pertussis Toxin—structure Cellular Uptake and Mode Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, it is not known how the unfolded PTS1 regains its active conformation in the cytosol. However, a crucial role of cellular protein folding helper enzymes for uptake of PTS1 into the host-cell cytosol has been demonstrated (see Section 3.1 ) [ 41 , 42 , 43 ].…”
Section: Pertussis Toxin—structure Cellular Uptake and Mode Of Actionmentioning
confidence: 99%
“…Therefore, we hypothesized that intracellular chaperones and protein folding helper enzymes might play a role for uptake and mode of action of PT. We showed that inhibitors of cellular chaperones protect cells from intoxication with PT [ 41 , 42 , 43 ]. We characterized the underlying mode of inhibition and demonstrated that chaperones of the heat shock family (Hsp90, Hsp70) and of the peptidyl prolyl cis/trans isomerase (PPIase) family (cyclophilins, Cyps and FK506-binding proteins, FKBPs) are required for the transport of the enzyme subunit of PT, as well as other ADP-ribosylating toxins into the target cell cytosol [ 58 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Novel Inhibitors Of Pertussis Toxinmentioning
confidence: 99%
See 1 more Smart Citation
“…PT enters cells through receptor-mediated endocytosis within clathrin-coated pits and follows the retrograde transport pathway through the Golgi apparatus into the endoplasmic reticulum (ER) [36][37][38]. From there, the unfolded S1 subunit translocates into cell cytosol through the ER-associated protein degradation (ERAD) retrotranslocon [39,40] with the assistance of the cytosolic chaperone cyclophilin [41,42]. Once in the cytosol, the S1 subunit catalyzes the transfer of the adenosine diphosphate (ADP)-ribose moiety of nicotinamide adenine dinucleotide (NAD + ) onto the Gα i/o inhibitory subunits of the heterotrimeric G-proteins, thus locking the various isoforms of Gα i/o inhibitory subunits in the inactive GDP-loaded state [43].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, small molecules have been identified which affect the endosomal maturation, 9 retrograde trafficking, 10 intracellular activatory proteolytic processing, 11 and intracellular chaperone-assisted activatory folding of exotoxins. 12 …”
mentioning
confidence: 99%